The Case for Diet: A Safe and Efficacious Strategy for Secondary Stroke Prevention - Dearborn, Jennifer L.; Urrutia, Victor C.; Kernan, Walter N. (Frontiers in Neurology, 2015)
Diet is strongly associated with risk for first stroke. In particular, observational and experimental research suggests that a Mediterranean-type diet may reduce risk for first ischemic stroke with an effect size comparable to statin therapy. These data for first ischemic stroke suggest that diet may also be associated with risk for recurrent stroke and that diet modification might represent an effective intervention for secondary prevention. However, research on dietary pattern after stroke is limited and direct experimental evidence for a therapeutic effect in secondary prevention does not exist. The uncertain state of science in this area is reflected in recent guidelines on secondary stroke prevention from the American Heart Association, in which the Mediterranean-type diet is listed with only a class IIa recommendation (level of evidence C). To change guidelines and practice, research is needed, starting with efforts to better define current nutritional practices of stroke patients. Food frequency questionnaires (FFQ) and mobile applications for real-time recording of intake are available for this purpose. Dietary strategies for secondary stroke prevention are low risk, high potential, and warrant further evaluation.